The Effects of Sport Activities and Environmentally Sustainable Behaviors on Subjective Well-Being: A Comparison Before and During COVID-19 - Wendtlandt, Mario; Wicker, Pamela (Frontiers in Sports and Active Living, 2021)
This study examined the effects of sport activities and environmentally sustainable behaviors on the subjective well-being of working-age adults (18–64). Specifically, it analyzes the effects of different types of sport activities, including nature-based, natural resource-using, and nature-neutral sport activities and different types of environmentally sustainable behaviors such as recycling, ecological consumption, energy-saving, and mobility on subjective well-being. The study conducts comparisons between the period before the COVID-19 pandemic and during the first lockdown in Germany. Quantitative survey data were collected using a convenience sampling approach (n = 412). Sport activities were captured with the number of hours spent on nature-based, natural resource-using, and nature-neutral activities. Environmentally sustainable behaviors were measured across four areas, including recycling, ecological consumption, energy-saving, and mobility. Subjective well-being was measured using the scale of the World Health Organization (WHO-5). Differences between the periods before and during COVID-19 were analyzed using t-tests. A set of multivariate regression models were estimated with subjective well-being as the dependent variable and sport activities, environmentally sustainable behaviors, and socio-demographics as independent variables. The results show that nature-based and nature-neutral sport activities significantly decreased during the first COVID-19 lockdown, while environmentally sustainable behaviors increased. The regression analyses reveal that nature-based and nature-neutral sport activities as well as ecological consumption significantly added to individuals' subjective well-being in the pre- and during-COVID-19-period. A decrease in nature-based and nature-neutral sport activities significantly predicted a decrease in individuals' subjective well-being. The findings of this study might help people understand the role and importance of active living for psychosocial outcomes during the COVID-19 pandemic.